Resistance of juvenile Nile tilapia Oreochromis niloticus from Brazilian populations to Streptococcus agalactiae (serotype Ib and ST-NT) - Oliveira-Neto, Rubens Ricardo; Mastrochirico-Filho, Vito Antonio; Assane, Inácio Mateus; Ariede, Raquel Belini; Freitas, Milena Vieira; Agudelo, John Fredy Gómez; Borges, Carolina Heloisa Souza; Gonçalves, Thaís Gornati; Lira, Lieschen Valeria Guerra; Reis Neto, Rafael V.; Pilarski, Fabiana; Hashimoto, Diogo Teruo (Frontiers in Aquaculture, 2024)
Nile tilapia is the main farmed fish in Brazilian aquaculture. Streptococcus agalactiae (GBS) is responsible for high mortality rates in fish farms. Genetic improvement is considered an effective alternative for producing resistant animals in aquaculture. The objective of this study was to estimate genetic parameters for resistance to GBS infection in a breeding population of Nile tilapia from Brazil, based on disease challenge using a circulating serotype (Ib and ST-NT). Furthermore, genetic correlations between resistance to GBS and average daily gain (ADG) were estimated to determine whether these traits can be included in selective breeding programs. Survival (SS) and time until death (TD) were the evaluated traits. The survival of the most resistant families was approximately 30%, indicating high phenotypic variation in resistance to the infection. Low to moderate heritability values for resistance traits in the Nile tilapia population were estimated, ranging from 0.14 to 0.27. Heritability for ADG was moderate to high (0.40) based on a growth trial involving 43 families (735 animals). Phenotypic correlations between the resistance traits (SS and TD) and ADG were positive and low, ranging from 0.09 to 0.18, whereas genetic correlations were close to zero. Phenotypic and genetic correlations between SS and TD were considered high and positive, ranging from 0.38 to 0.72. The results suggest that selection for resistance against GBS does not negatively affect juvenile weight gain in Nile tilapia.